1997
DOI: 10.1073/pnas.94.17.9191
|View full text |Cite
|
Sign up to set email alerts
|

Typing of urinary JC virus DNA offers a novel means of tracing human migrations

Abstract: Although polyomavirus JC (JCV) is the proven pathogen of progressive multifocal leukoencephalopathy, the fatal demyelinating disease, this virus is ubiquitous as a usually harmless symbiote among human beings. JCV propagates in the adult kidney and excretes its progeny in urine, from which JCV DNA can readily be recovered. The main mode of transmission of JCV is from parents to children through long cohabitation. In this study, we collected a substantial number of urine samples from native inhabitants of 34 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
160
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 180 publications
(177 citation statements)
references
References 40 publications
13
160
0
1
Order By: Relevance
“…Based on sequence analysis of JCV complete genomes, as well as segments of the VP1 and T antigen genes, JCV can be classified into several geographically based genotypes and subtypes (Ault & Stoner 1992, Agostini et al 1995, 1997d, Sugimoto et al 1997. The major genotypes so far described are Type 1, which is of European origin, Type 2, which is Asian, and Types 3 and 6 which are African in origin (Agostini et al 1995(Agostini et al , 1998.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on sequence analysis of JCV complete genomes, as well as segments of the VP1 and T antigen genes, JCV can be classified into several geographically based genotypes and subtypes (Ault & Stoner 1992, Agostini et al 1995, 1997d, Sugimoto et al 1997. The major genotypes so far described are Type 1, which is of European origin, Type 2, which is Asian, and Types 3 and 6 which are African in origin (Agostini et al 1995(Agostini et al , 1998.…”
mentioning
confidence: 99%
“…This is followed by persistent infection of the kidneys from which JCV is excreted in urine. Studies with polymerase chain reaction (PCR) show that 30-70% of adults worldwide are positive for JC viruria (Agostini et al 1996, Sugimoto et al 1997, Shah et al 1998. JCV has been established as the causative agent in progressive multifocal leukoencephalopathy (PML), a fatal demyelinating disease of the central nervous system (Zurhein & Chou 1965).…”
mentioning
confidence: 99%
“…In the current study, we focused our attention on an Asian genotype of JCPyV named SC. Sugimoto et al (1997) found that this genotype occurs mainly in southeastern Asia and southern China, with minor SC isolates in central and northern Asia and southern Africa. Using phylogenetic analysis based on complete viral DNA sequences, Saruwatari et al (2002b) subclassified many SC isolates in Myanmar, together with a few in other countries, into six subgroups, SC-a to -f. Most subgroups (SC-a to -e) contained isolates in Myanmar, but one (SC-f) included isolates in various regions of southeastern Asia and southern China.…”
Section: Introductionmentioning
confidence: 93%
“…southern Africa and southern Japan) remote from the areas where SC is most common (i.e. Southeast Asia), although these were detected at only a low frequency (Sugimoto et al, 1997;Kitamura et al, 1998); (6) most SC isolates in Guam probably belonged to the SC-f subgroup, as these had the unique pentanucleotide deletion in the regulatory region (see above). In addition, a single isolate in Hawaii was grouped in the non-SC-f category based on the SNP analysis, consistent with the phylogenetic analysis of the complete viral DNA sequences described above.…”
Section: Classification Of Sc Isolates Worldwide Into Sc-f and Non-scmentioning
confidence: 99%
See 1 more Smart Citation